Optimization of intelligent financial management system based on blockchain and internet of things - Shitong Huang (Scientific Reports)
Abstract To address the challenges of low efficiency, complex processes, low accuracy, and high costs in financial management, this paper proposes utilizing blockchain and IoT technologies, specifically Blockchain-based Smart Contract and Biometric Multifactor Authentication (BCSC-BMFA), to develop an intelligent financial management system for technical institutions. The proposed BMFA system aims to provide secure and transparent data management, real-time monitoring and reporting, and automation of financial processes to improve accuracy, efficiency, and transparency. Blockchain-based ledgers are used to store financial data securely, along with IoT sensors such as Point-of-Sale (POS) sensors and asset tracking sensors, to capture real-time financial data, and smart contracts to automate financial processes. This framework improves accuracy and efficiency, reduces costs, and increases transparency and accountability. The system’s efficiency is evaluated using a pilot study to demonstrate its performance and effectiveness in a real-world scenario.